Penerapan Prinsip Kehati-hatian (Prudential Principle) dalam Pembiayaan Murabahah pada PT Bank BRISyariah : Studi Deskriptif Pada PT Bank BRISyariah Kantor Pusat - Muhtar .; Isfandayani . (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2015)
The research objective of this study was to determine the application of Prudential Principle in murabaha financing at PT. Bank BRISyariah: Descriptive Study at Head Office PT. Bank BRISyariah. This study concludes that the purpose of the application of the precautionary principle in order to maintain the health, safety, and stability of national banking systems. In applying the prudential principle all employees of Bank BRI Syariah participate in applying the precautionary principle ranging from employees, directors, commissioners, sharia supervisory board, shareholders and affiliated parties. The application in murabaha financing at Bank has BRISyariah properly implemented, can be found at: Sides in accordance with the law of positive law and administrative law of shariah. And also, murabaha financing can assist banks know your customer and know the purpose of the customer makes a request for financing snd administration of murabaha financing, among others, the financing application documents and financing documents after disetujui.Sisi procedures murabaha financing made by the Bank BRISyariah quite a lot in order to carry out the prudential principle, reflected in the request for funding to finance monitoring. The Bank's risk management side BRISyariah two working unit of risk, ie work unit in charge of operational risk to mitigate operational risk and funding risk duty to mitigate financing risk.